PROTECTION OF SOCIAL VALUES AND RELATIONS PROTECTED BY CRIMINAL LAW - Popoviciu, Laura-Roxana (International Journal of Legal and Social Order, 2022)
This article deals with the particular aspects regarding the protection that criminal law norms grant to social values and relations, which is precisely the object of criminal law. As the main instrument of the criminal policy, the criminal law aims to defend the state and all the people who are at a given moment in the national territory, against the criminal phenomenon. A condition of the existence of human society was and is the need to defend social values through a system of relationships formed between members of society in such a way as to succeed in their achievement and normal evolution. The system for the defense of social values has a binding force against people who carry out dangerous actions for society and defines the crime, the forms of criminal liability and the sanctions that are applied when crimes are committed by violating the criminal rules. How is the protection provided by the criminal law with regard to social values achieved?By means of the two essential requirements that the criminal rules claim: firstly, the requirement required of all persons who are at a given time in the territory to which the law has its applicability and who are its recipients. All of them are obliged to conform their conduct to the requirements that the criminal law provides. And last but not least, the state bodies that must ensure criminal liability when the criminal law has been violated and crimes have been committed. Through the rules of the criminal law, the values and social relations that are formed around these values are promoted and protected. In this way, the protection of society in general is achieved. Criminal law criminalizes crimes, which are the most serious social acts because they affect the most important social values.